Gotham Academy. Volume 1, Welcome to Gotham Academy - Cloonan, Becky; Fletcher, Brenden (DC Comics, 2015)
Olive Silverlock arrives at Gotham Academy with amnesia and a fear of bats. When she tries to show new student Maps Mizoguchi around, they encounter a ghost haunting campus and a secret society conducting strange rituals.